How to merge courses via Skype™? Lessons from an International Blended Learning Project - Yasemin Akbaba; Filiz Başkan (Association for Learning Technology, 2017)
This study reports on an international project in which students taking the course Contemporary Issues in Turkish Politics in spring 2011 and fall 2011 at two institutions of higher education, 'Gettysburg College' in the United States and 'Izmir University of Economics' in Turkey, worked together in virtual learning environments to complete various tasks as part of their course work. The project employed a blend of traditional and technology-based teaching methods in order to introduce a technology like Skype in a bi-national learning environment in Turkey. Students collaborated and interacted with their international counterparts in two different virtual contexts. First, classrooms in the two countries were merged via Skype three times to conduct classroom-to-classroom discussion sessions on Turkish politics. Second, students were paired across locations to work on several assignments. In this paper, our goal is to present how Skype is used in a bi-national context as a blended teaching tool in an upper-level college course for instructors pursuing a similar exercise. In addition to outlining the process with a focus on Skype discussions and one-on-one student projects, we provide actual assignments and discussion questions. Students' views elicited through surveys administered throughout the semester are presented alongside anecdotal evidence to reflect how the project was received.